Manajemen Segregasi Gender Tunggal dalam Membina Karakter Kemandirian Peserta Didik di SMP Negeri I Maja Kabupaten Majalengka - Suhaedi, Agus Edi; Widiantari, Dian; Nugraha, Firman (Permata : Jurnal Pendidikan Agama Islam, 2022)
Changes in the environment in the education unit has been so dynamic that forced to make changes to the vision and mission and strategy. Parents, educators and all parties involved in education complain why character education in Indonesia has not shown encouraging results. The occurrence of violations committed by students is one indication of the need for an educational management model. This study aims to analyze the class separation program in fostering the character of students. This study uses a qualitative approach with a case study model and purposive sampling data sources include principals, vice principals, teachers and parents of students. The instruments that the authors use are in-depth interviews, observation and documentation studies and triangulation. Data analyst by compiling and preparing data, reading the entire data, coding the data, applying coding, analyzing the coding results, and interpreting the theme and description. Validity of data with credibility test, transferability, confirmability and depenability. Planning begins with knowing the background of the program, curriculum Foundation, curriculum design. Analyze the organization of a single gender segregation program that all educators and education personnel entirely support a single gender sergregation program. This Program is implemented only in teaching and learning activities only. The effect of single gender sergregation can be seen from participants focusing more on learning, as well as the focus of control on improving the character of independence.Keyword: Management; Single Gender Segregation; Character Education. Abstrak Perubahan lingkungan di satuan pendidikan sudah sedemikian dinamis yang memaksa melakukan perubahan terhadap visi dan misi serta strategi. Para orang tua, pendidik dan semua pihak yang terlibat dalam pendidikan mengeluhkan mengapa pendidikan karakter di Indonesia belum menunjukan hasil yang menggembirakan. Terjadinya pelanggaran-pelanggaran yang dilakukan oleh pelajar salah satu indikasi perlunya sebuah model pengelolaan pendidikan. Penelitian ini bertujuan untuk menganalisis program pemisahan kelas dalam membina karakter peserta didik. Penelitian ini menggunakan pendekatan kualitatif dengan model studi kasus dan sumber data purposive sampling meliputi Kepala Sekolah, Wakil Kepala Sekolah, guru dan orang tua siswa. Instrumen yang penulis gunakan adalah wawancara mendalam, observasi dan studi dokumentasi serta trianggulasi. Analis data dengan cara menyusun dan mempersiapkan data, membaca keseluruhan data, memberi kode data, menerapkan coding, menganalisis hasil coding, serta memaknai tema dan deskripsi. Keabsahan data dengan uji kredibilitas, transferabilitas, konfirmabilitas serta depenabilitas.Perencanaan diawali dengan mengetahui latar belakang program, landaskan kurikulum, desain kurikulum. Menganalisis pengorganisasian program segregasi gender tunggal bahwa semua tenaga pendidik serta tenaga kependidikan seluruhnya mendukung program sergregasi gender tunggal. Program ini dilaksanakan hanya pada kegiatan belajar mengajar saja. Pengaruh sergregasi gender tunggal terlihat dari peserta lebih fokus belajar, serta fokus pengendalian terhadap peningkatan karakter kemandirian.Kata Kunci: Manajemen; Segregasi Gender Tunggal; Pendidikan Karakter.